Association analysis of Mycoplasma pneumoniae 23S rRNA gene mutation with refractory Mycoplasma pneumoniae pneumonia in children - Wen Li; Wei Gao; Xiaoyu Xiong; Xuan Tang; Aimin Li (PLoS ONE, 2026)
Objective This study investigates the current status of macrolide resistance in Mycoplasma pneumoniae (MP) and analyzes the relationship between mutations at the 23S rRNA A2063G and/or A2064G loci and refractory Mycoplasma pneumoniae pneumonia (RMPP). Methods A retrospective analysis was conducted on 205 hospitalized children diagnosed with MPP at the Third Ward of the department of paediatrics, Jingzhou Central Hospital, from October 2023 to October 2024. Diagnosis was confirmed by pharyngeal MP nucleic acid testing and MP antibody titers ( MP -Ab ≥ 1:160). All patients were screened for macrolide-resistant gene mutations (A2063G/A2064G). Patients were categorized based on the presence of macrolide-resistant gene mutations and RMPP diagnosis. Clinical features, laboratory results, and treatments were compared between groups. Multiple logistic regression was used to identify independent risk factors for RMPP. Results Among 205 children with MPP, 157 (76.6%) harbored A2063G/A2064G mutations. Of the 77 children with RMPP, 71 (92.2%) carried these mutations, showing a significant association ( P < 0.05). Compared to the non-resistant group, children with resistant mutations had prolonged fever duration, delayed defervescence after azithromycin, and required more bronchoscopic alveolar lavage ( P < 0.05). The RMPP group exhibited more severe symptoms, longer fever and hospital stays, higher inflammatory markers (CRP, LDH, D-dimer, ESR, PCT; P < 0.001), and more frequent pulmonary consolidation, pleural effusion, plastic bronchitis, and extrapulmonary involvement. Multivariate analysis identified macrolide-resistant mutations, fever duration, and D-dimer level as independent risk factors for RMPP. Conclusion The widespread macrolide resistance in M. pneumoniae (76.6% in this cohort) was associated with point mutations at the A2063G and/or A2064G loci in the 23S rRNA gene. The development of RMPP is linked to macrolide-resistant mutations, duration of fever and D-dimer levels. D-dimer emerged as the most predictive risk factor.